Pengaruh Pemberian Buah Naga Merah Pada Ibu Hamil Terhadap Peningkatan Hemoglobin Di Wilayah Kerja UPT. Puskesmas Sambau Kota Batam 2023 - Rifka Faradiba; Norma Jeepi; Rofiqo larasati Philip (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
During pregnancy, pregnant women experience changes that occur physiologically, one of which is changes in the cardiovascular system which results in a blood volume greater than the growth of blood cells, then hemodilution or blood thinning occurs, causing a decrease in hemoglobin levels which results in pregnant women being anemic. World Health Organization (WHO) 4.5%? 10,000 Maternal Deaths worldwide are caused by anemia. The general research objective of this study was to determine whether there was an effect of giving red dragon fruit on increasing hemoglobin in pregnant women at Sambau Health Center, Batam City. This type of research is Pre-Experimental with one group Pre-test Post-test design. The sampling technique used was purposive sampling with 15 pregnant women respondents, each respondent was given the same treatment by giving dragon fruit as much as 100 grams per day on the first day. Measurements were carried out 2 times once during 7 days of treatment and the last measurement was on day 14. The results of the analysis using the Paired sample t-test analysis showed that the data was fig (2-tailed 0.000 < 0.05, so H0 was rejected and Ha was accepted, which means there is The effect of giving dragon fruit to pregnant women on increasing hemoglobin. It is recommended that health workers be able to pay attention and recommend the consumption of fruit rich in iron, one of which is giving red dragon fruit to help increase hemoglobin levels.